1998
DOI: 10.2527/1998.762513x
|View full text |Cite
|
Sign up to set email alerts
|

Essential and nonessential amino acid composition of pigs from birth to 145 kilograms of body weight, and comparison to other studies.

Abstract: The amino acid composition of the body components (carcass, hair, whole blood, and a composite of the other body tissues) were determined from a total of 81 crossbred pigs at 10 weight intervals from birth to 145 kg body weight. Body component amino acid compositions (g/100 g protein) were multiplied by their respective protein contents, resulting in calculated whole-body amino acid compositions. From 8.5 to 145 kg body weight, the amino acid compositions were similar within each body component but differed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 14 publications
6
64
1
1
Order By: Relevance
“…The content of essential AA in the skin is very low, and the skin (without bristles) contains <1.5% TSAA. However, bristles contain ∼13% Cys on a weight basis and more than 7% of the whole body Cys content may be found in bristles (Mahan and Shields, 1998). Calculated from the wholesale cuts (Daumas, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The content of essential AA in the skin is very low, and the skin (without bristles) contains <1.5% TSAA. However, bristles contain ∼13% Cys on a weight basis and more than 7% of the whole body Cys content may be found in bristles (Mahan and Shields, 1998). Calculated from the wholesale cuts (Daumas, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In their study of the amino acid composition of protein gain from 8 to 21 days of age, the aforementioned authors found significantly higher levels of lysine, methionine, alanine, aspartic acid, glutamic acid and glycine in broilers than in laying-type chickens. While the increased deposition of lysine may be explained by its higher concentration in muscle protein (Mahan and Shields, 1998), the role of nonessential amino acids is less clear. It is interesting to note that, unlike the present study, Fatufe et al (2004) reported no significant effect of genotype on threonine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some doubts concerning the validity of this hypothesis (Gahl et al, 1995). Changes in whole body amino acid composition have been related to growth rate (Kyriazakis et al, 1993;Mahan and Shields, 1998), protein and energy intake (Bikker et al, 1994) and amino acid content in the diet (van Milgen et al, 2007). According to Chung and Baker (1992b), the variation in amino acid composition of whole body protein may be due to the retention of different types of proteins that differ in amino acid composition.…”
Section: Introductionmentioning
confidence: 99%